2017
DOI: 10.17844/jphpi.v19i3.15101
|View full text |Cite
|
Sign up to set email alerts
|

The Effectivity of Marine Bio-activator and Surimi Liquid Waste Addition of Characteristics Liquid Organic Fertilizer from Sargassum sp.

Abstract: <p>Abstract<br />Organic fertilizer is highly recommended for soil and plant because it can improve the productivity and repair physical, chemical, and biological of soil. Sargassum sp. and surimi liquid wastes contain organic matter and nutrient needed by plants and soils. The addition of marine bio-activator which contains bacterial isolates from litter mangrove serves to accelerate the composting time and increases the activity of microorganisms in the decomposition process. The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…These results are in accordance with the criteria for mature compost according to SNI 197030-2004, namely 27-58%. This is in accordance with research Ratrinia et al [18], which states that the decrease in C-organic concentration is due to the use of carbon by microorganisms as an energy source to decompose organic matter.…”
Section: C-organic Contentsupporting
confidence: 93%
“…These results are in accordance with the criteria for mature compost according to SNI 197030-2004, namely 27-58%. This is in accordance with research Ratrinia et al [18], which states that the decrease in C-organic concentration is due to the use of carbon by microorganisms as an energy source to decompose organic matter.…”
Section: C-organic Contentsupporting
confidence: 93%
“…When microorganisms have adapted to the new conditions, their cells grow faster and consume nitrogen supplies resulting in decreasing nitrogen levels in the environment. Ratrinia et al (2016) stated that the best condition for fertiliz-er fermentation is in a semi-anaerobic condition within a closed container and is fermented for about seven days. In this phase, the nitrogen content in the fertilizer is quite high and is related to the number and activity of microbes.…”
Section: Resultsmentioning
confidence: 99%
“…starter was added to accelerate the fermentation, followed by the addition of 100 grams of fish powder 1 L distilled water as the solvent and 20 ml of sugar solution (Karim et al, 2014) . According to Ratrinia et al, (2016) , the fermentation process takes place in a semi-anaerobic condition inside a closed container for approximately seven days.…”
Section: Gracilaria Sp Liquid Organic Fertilizer Productionmentioning
confidence: 99%
“…L. leucocephala belongs to the family Leguminosae [54]. According to Ratrinia [55], white leadtree leaves contain essential nutrients that are required for plant growth and development. Kurniati [56] reported that the addition of L. leucocephala leaves would increase C levels in liquid organic fertilizers.…”
Section: White Lead Treementioning
confidence: 99%